DOI: 10.31274/etd-180810-3661
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate distribution and turnover affects soil microbial ecology and ecosystem processes in three bioenergy systems

Abstract: approach to answering them. They have also made the process a lot more fun. My colleagues in the Hofmockel Lab deserve much credit for teaching and assisting me throughout the years, most especially Sarah Hargreaves and Ryan Williams. The numerous and enthusiastic undergraduate assistants have provide invaluable assistance and kept me excited about coming back to the lab every day. Thank you Eric Asbe, Meghan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 172 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…This accelerates the process of C oxidation, expels organic matter trapped in soil aggregates, and increases the amount of C in the soil in the form of CO 2 . Previous studies (Bach, 2014; Liu, Han, Li, et al, 2019; Liu, Han, & Zhang, 2019) have shown that compared with perennial rangelands, the main factor in reducing carbon in cultivated lands can be related to SOC in the form of CO 2 . CR land abandonment over the time‐chrono sequence of the abandonment could also improve SOC and the total N in the Sheida region with an increase in the time of land abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…This accelerates the process of C oxidation, expels organic matter trapped in soil aggregates, and increases the amount of C in the soil in the form of CO 2 . Previous studies (Bach, 2014; Liu, Han, Li, et al, 2019; Liu, Han, & Zhang, 2019) have shown that compared with perennial rangelands, the main factor in reducing carbon in cultivated lands can be related to SOC in the form of CO 2 . CR land abandonment over the time‐chrono sequence of the abandonment could also improve SOC and the total N in the Sheida region with an increase in the time of land abandonment.…”
Section: Discussionmentioning
confidence: 99%